Description of growth and body composition of freshwater angelfish (Pterophyllum scalare) by Gompertz model - Helena Espitia-Manrique, Carmen; Kochenborger Fernandes, Joao Batista [UNESP]; Sakomura, Nilva Kazue [UNESP]; Arias-Vigoya, Angel Andres [UNESP]; Torres do Nascimento, Thiago Matias [UNESP]; Silva, Edney Pereira da [UNESP]; Menegasso Mansano, Cleber Fernando [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2017)
The objective of this study was to describe the growth of freshwater angelfish (Pterophyllum scalare) using the Gompertz model, determining the relative growth and allometric coefficients of body components in relation to body weight and protein weight. Six hundred animals were grown until 233 days of age. Data on chemical composition (water, lipid, protein, and ash) and weight measurements were obtained each 30 days. The Gompertz growth equation was used to analyze chemical allometry and to estimate growth parameters. The relationship between chemical components and body protein was estimated. Protein and body weight increased proportionally, with ash being the earliest nutrient (209.2 days), while lipid deposition occurred later. Linear regression analysis showed an inverse relationship between lipids and body water. This study provided a useful equation to predict the growth, chemical body composition, and rate of nutrient deposition across the life stages of freshwater angelfish. The rates of nutrient deposition as a function of body weight are important to understand the growth process of freshwater angelfish. Thus, mature weight was estimated in 26.14 g. The allometric relationships of body components and deposition rates indicated that protein and body weight are highly correlated across the life stages of freshwater angelfish. The Gompertz equation is a useful tool to describe the growth and body composition of freshwater angelfish.
Keywords: allometry; growth curve; ornamental fish